Hemiconvulsion-Hemiplegia-Epilepsy Syndrome in Adult with Uncontrolled Seizures and Phenytoin Toxicity - Athwal, Pal Satyajit Singh (Cureus, 2020)
Hemiconvulsion-hemiplegia-epilepsy (HHE) syndrome is a rare condition, characterized by sudden onset of unilateral seizures leading to cerebral hemisphere atrophy and hemiplegia which might persist for lifetime. It is believed to be outcome of prolonged or unmanaged status epilepticus in pediatric age group. HHE is diagnosed during childhood but we report an undiagnosed case of 30-year-old male who was dealing with uncontrolled seizure, phenytoin toxicity and hemiparesis. He was diagnosed with HHE based on characteristic imaging findings leading to complete alteration of management and opened wide array of surgical options to manage this debilitating condition.